Cloud outsourcing computing security protocol of matrix multiplication computation based on similarity transformation. (2018) - Kong, Shanshan; Cai, Yongquan; Xue, Fei; Yu, Haiyang; Ditta, Allah
With the emergence of the cloud computing paradigm in scientific and business applications, computation outsourcing to the cloud has become a popular application in the age of cloud computing. However, this computing paradigm brings in some new security concerns and challenges, such as input/output privacy and result verifiability. In this paper we use similar transformation of matrix to design secure verifiable and practical outsourcing protocol for matrix multiplication calculation. Compared with those existing outsourcing protocols, our protocol has obvious improvement concerning both efficiency and security. In order to check the correctness of the result returned from the cloud, an efficient verification algorithm is employed. Computational complexity analysis shows that our protocol is highly efficient.